THE ROLE OF EDUCATIONAL PHILOSOPHY AS THE FOUNDATION FOR TEACHER STRENGTHENING IN SCHOOLS - Fadhilah Khairani; Tuti Handayani; Darwin Effendi; Yenny Puspita (Universitas PGRI Palembang, 2023)
Education is one of the most important things in life, where there is a process of seeking information so that those who initially don't know become familiar with it, and those who don't understand become familiar with it. To educate people and make them knowledgeable, humans known as teachers or educators are needed. This study uses the library research method, which aims to collect information relevant to the problem or topic being studied. The information obtained comes from research reports, scientific books, scientific essays, theses and dissertations, statutes, regulations, yearbooks, encyclopedias, and other written sources, both printed and from other electronic sources. Overall, the authors can conclude that philosophy plays an important role as a basis for strengthening teaching in schools. Educational philosophy can provide guidance to teachers in carrying out their roles and obligations as educators who are encouraged and imitated in teaching and learning activities in schools, especially in the classroom.